O WYZWANIACH DLA POLSKIEGO MEDIOZNAWSTWA W KONTEKŚCIE AKSJOLOGII, PROFESJONALIZMU DZIENNIKARSKIEGO, METODOLOGII BADAŃ ORAZ TOŻSAMOŚCI DZIENNIKARSKIEJ - Gackowski, Tomasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article was written under the influence of reflections made in the course of reading the latest monograph of prof. Jacek Dąbała titled: Media and Journalism. Axiology – workshop – Identity, ed. Universitas, Cracow 2014. Text on the one hand seems to be a review, on the other hand it is polemics, in which writing these words decided to even develop a kind of specific problems that interested him. In this context, this article touches on issues such as the axiology of the media and now these anti-values , telegenity of presenters/journalists and its consequences for reception by the public of mass media, contemporary journalistic workshop, its capabilities and limitations, the function of theology in the media, journalistic professionalism and the greatest contemporary threats to him, the study of audiovisual methods with particular emphasis on the phenomenological approach, and finally the identity of the journalist as a cognitive construct, the operating mechanism of the mass media’s recipients and the subject of media research media studies. This text should be treated as a voice in the discussion, initiated by prof. Jacek Dąbała on ponderable issues which are not always perceived by the Polish media experts.